Hepatitis D virus infection in Slovenian patients with chronic hepatitis B virus infection - Jelen, Mateja (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2016)
Introduction: Of the 350 million individuals chronically infected with hepatitis B virus (HBV) worldwide, approximately 15 to 20 million have been exposed to hepatitis D virus (HDV). This study determined for the first time the HDV prevalence in Slovenian patients with chronic HBV infection. In addition, a literature search was performed to identify all HDV prevalence studies from European countries. Methods: A total of 1,305 HBsAg-positive serum samples, obtained from the same number of patients, were randomly selected from 2,337 patients referred to the Slovenian national reference laboratory for viral hepatitis between 1998 and 2015. All samples were retrospectively tested for the presence of total anti-HDV antibodies. Anti-HDV-positive patients were additionally tested for the presence of anti-HDV IgM antibodies, HDV antigen, and HDV RNA. Results: Total anti-HDV antibodies were detected in three of the 1,305 patients tested (0.23%; 95% CI: 0.08-0.67%), of whom one patient had recovered from the past HDV infection and two patients had an ongoing chronic HDV infection. The literature search identified 36 peer-reviewed HDV prevalence studies published between 1983 and 2016 and originating from 21 European countries. Conclusion: The observed prevalence of HDV infection in Slovenia was among the lowest reported in Europe and worldwide. Due to the observed low prevalence of HDV infection, routine diagnostic testing for HDV should not be considered in differential diagnosis of exacerbation of liver disease in Slovenian patients with chronic HBV infection.
Keywords: hepatitis D; virusne infekcije